Intelligent Systems Design and Applications 19th International Conference on Intelligent Systems Design and Applications (ISDA 2019) held December 3-5, 2019 - Abraham, Ajith; Siarry, Patrick; Ma, Kun; Kaklauskas, Arturas (Advances in Intelligent Systems and Computing, 2021)
XVI, 663 p. 308 illus., 207 illus. in color.